IMPLEMENTASI PROGRAM KAMPUNG KELUARGA BERKUALITAS (KB) BERKELANJUTAN DI DESA NONGKODONO DAN KAMPUNG KELUARGA BERKUALITAS (KB) BERKEMBANG DI DESA KARANGLO KIDUL KABUPATEN PONOROGO - Fitriani, Lisa Dwi; Ridho, Irvan Nur; Hilman, Yusuf Adam; Triono, Bambang (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2025)
The purpose of this study is to provide an overview of how the implementation of the sustainable family planning village programme in Nongkodono Village and the developing family planning village in Karanglo Kidul Village, Ponorogo Regency. This research is descriptive qualitative research, with data collection techniques including: observation, interviews, and documentation, using a data analysis model with the following sequence: data reduction, data presentation, and conclusion drawing. The implementation of Sustainable KB Village shows how the programme focuses on preserving and developing existing initiatives by involving all elements of the community and ensuring the continued involvement of various parties. The implications for residents include improved welfare through economic empowerment programmes, better access to health care, and a deeper understanding of reproductive health and family planning, all of which contribute to an improved quality of life. Meanwhile, Kampung KB Berkembang is in the development phase and focuses on increasing community participation and strengthening infrastructure and services that support family health and welfare. The implications for residents include improved access to health services and education, as well as increased social participation leading to a more cohesive and supportive community. the two programmes have similarities in terms of best practices in the implementation of this programme including active community participation, collaboration with various stakeholders, and continuous education. Constraints to the programme include low initial participation, limited resources, and challenges in socialisation effectiveness. The benefits of the programme are good, including improved quality of life, population growth control, and more equitable welfare for village communities, which ultimately creates a long-term sustainable positive impact